Penanaman Kaliandra Sebagai Kayu Energi dan Hijauan Makanan Ternak Pada Pertanaman Agroforestri Masyarakat Desa Gerbosari, Samigaluh Kulon Progo - Eko Prasetyo; Wiyono Wiyono; Puji Lestari; Rochmat Hidayat; Silvi Nur Oktalina; Agus Ngadianto; Prasetyo Nugroho (Jurnal Pengabdian dan Pengembangan Masyarakat, 2018)
The purposes of community service entitled "Kaliandra Planting as Energy Wood and Forage Livestock Feed on Agroforestry Crops Gerbosari Village Community Samigaluh Kulon Progo" are 1). To provide additional knowledge of Kaliandra (Calliandracallothyrsus) utilisation other than HMT that is as a raw material of energy source and 2). To practice the technique of Kaliandra planting on agroforestry system in Gerbosari Village. The way cattle developed in Dusun Keceme is "cut and carry system" or grazing system. Grazing systems make farmers provide land for HMT planting either in the form of grass or tree leaves. Public dissemination and discussion with the community resulted in an agreement that the program is not only Kaliandra planting, but the utilisation of Kaliandra as an energy wood and wood pellet introduction is needed by Keceme Hamlet community. Methods of implementation of community service are through 4 stages in one unity of scheme. The methods are 1) program dissemination, 2) counselling, 3) practice of using a wood pellet stove and 4) planting. The community service program can provide an initial understanding of the community of Keceme Hamlet about the benefits of Kaliandra as an alternative to renewable energy that is in the form of wood pellets. The technique of agroforestry cultivation of Kaliandra has long been practised by the people of Keceme Hamlet that is on the edge of the terrace of the land.